PERTUMBUHAN AWAL KAYU MERAH (Pterocarpus indicus Willd) PADA PLOT KONSERVASI EX-SITU DI GUNUNGKIDUL UMUR 2 TAHUN - Yuliah Yuliah; Ari Fiani; Tri Pamungkas (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2020)
Ex-situ conservation plot of kayu merah (Pterocarpus indicus Willd) has been established in Gunungkidul in2016. The purpose of this study was to observe the early growth of kayu merah in the plot at 2 years old. The plot was laid-out in randomized complete block design consisting of 68 families, 4 tree-plot and 5 blocks with spacing of 3 m × 3 m. Genetic materials of kayu merah were collected from 3 populations namely Timor, Flores and Seram. Measurement was conducted in survival rate, tree diameter, tree height and number of branches. The result showed that the average survival rate of family was high (≥80%). Based on the populations, the survival rate of Timor, Flores and Seram were around 95%, 96% and 96.5% respectively. The average height, diameter and number of branches were 275 cm, 2.79 cm and 1.66, respectively. There were significant differences for height, diameter and number of branches among the tested families. In general, family ranking varied among the measured traits. Correlation between the traits varied among the populations. The Seram population showed the top family ranking for all the traits. It indicated that characterization in ex-situ conservation plot using genetic materials collected from the three populations was important for further conservation program of kayu merah.